Hubungan antara Kemampuan Berpikir Kritis dengan Kemampuan Berpikir Kreatif Siswa pada Materi Ekologi - Mayarni Mayarni; Yuni Yulianti (University of Bengkulu, 2020)
In the age of 21st century, education is faced with increasingly severe challenges. One of the challenges is to produce human resources who have the ability to face the full range of challenges in life. Competence in the 2.1 century is called 4C which includes the ability to think critically and solve problems (Critical Thinking and Problem Solving), creative thinking (Creativity), communication skills (Communication Skills), and the ability to work together (Ability to Work Collaboratively). to test the closeness between critical thinking and creative thinking on ecological material; Two classes were used in data collection, totaling 36 students, 25 of which were female and 11 were male with an age range of 15 to 17 years and were obtained by simple random sampling technique; Data were collected from the test instrument for critical and creative thinking questions and then analyzed by the regression equation Y for X, the linearity and significance test Y for X, the correlation coefficient and the significance test for the correlation coefficient Y over X; This study obtained the results that show that the relationship is linear with a correlation value of 0.724 which is classified as a strong level of closeness so that the value of the contribution of critical thinking skills to creative is 52.42%; The relationship between the ability to think critically towards creative thinking with the contribution of critical thinking skills to the ability to think creatively is 52.42%.